Optimal Policies and Immiserizing Growth - Bhagwati, Jagdish N. (American Economic Review, 1969)
In 1938, the author analysed the paradoxical case of immiserizing growth where a country, with monopoly power in trade, found that the growth-induced deterioration in its terms of trade implied a sufficiently large loss of welfare to outweigh the primary gain from growth. An obvious corollary of this proposition was that, if the country imposed an optimum tariff this paradox would be eliminated. The original immiserizing growth phenomenon belongs to the class of cases where a welfare-reducing distortion in the economy is the cause of the immiseration. Since the primary cause of the immiseration is the reduction in gains from trade resulting from shifts in the foreign offer curve facing the country, even though optimal policies are being followed before and after growth, there is no possibility of devising policies to escape such immiseration. The reduction in gains from trade, required to produce immiseration, would merely have to be larger than in the case where the initial pre-growth situation is optimal and hence characterised by a higher welfare level.